Ukraine : Technical Assistance Report-Reducing Social Security Contributions and Improving the Corporate and Small Business Tax System. (IMF Staff Country Reports; Country Report ;, 2016)
This paper discusses four key issues, which are closely connected, on tax policy in Ukraine. These issues are social security contribution (SSC), the simplified tax regime for small taxpayers, the corporate profit tax, and excise tax. Ukraine's SSC rates are very high, which are associated with an oversized informal sector that erodes the tax base, while the simplified tax regime for small taxpayers provides inordinate benefits that weaken the tax system and is prone to abuse. Corporate profit tax revenue has declined to its lowest level since 2006 and is now well below the regional average. Excise taxes have become an important revenue source, but remain low by international standards.